Alkaline treatment for preventing acidosis in the rumen culture fermenting carbohydrates: An experimental study in vitro - Darwin, -; Blignaut, David (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The current research was carried out to evaluate the use of magnesium hydroxide as buffer to control acidosis in rumen culture fermenting carbohydrates in vitro. Materials and Methods: The experiments were carried out in the chemostat system in which the reactor used was a 200 ml of working volume. A series of fed-batch trials were carried out in fed-batch system with hydraulic retention time of 4 days. All digesters were completely mixed with the rotation of 55 rpm, and the temperature was controlled at 39°C ± 0.5°C. Results: Results showed that the supplementation of magnesium hydroxide (50 mM/day) to the corn starch feed (12.5 gm/l per day) for the rumen culture could prevent acidosis while at the same concentration of sodium bicarbonate addition to rumen culture, acidosis cannot be prevented in which lactic acid accumulated up to 200 mM. Supplementing magnesium hydroxide to the mixture of starch and sugar feeds prevented acidosis in which the major fermentation end product formed was acetate. A daily feeding with the ratio of 4.5:1 [starch: Mg(OH)2] was feasible to prevent rumen acidosis. Conclusion: Magnesium hydroxide added to the rumen culture could prevent lactic acid accumulation while sodium bicarbonate supplementation did not prevent acidosis and had lactic acid accumulation. J. Adv. Vet. Anim. Res., 6(1): 100-107, March 2019